Return to sport criteria for musculoskeletal injuries in high-performance athletes: a qualitative analysis - Hassan, R.; D`ettorre, D.; Poku, D. (Research in Sports Medicine, 2025)
The aim of this study was to explore criteria for return to sport (RTS) across physical, psychological, social, and contextual domains from the perspectives of key decision-makers. In-depth semi-structured interviews were conducted with 15 clinicians [9 physiotherapists, 6 Sport and Exercise Medicine (SEM) doctors] working in elite-level clubs across Europe and Asia, averaging 70 minutes per interview. Data were transcribed, thematically analysed using the framework method, and triangulated with participants. Three core themes were identified: 1) definitions of RTS, 2) actors and processes, and 3) criteria for RTS. SEM doctors and physiotherapists were viewed as pivotal decision-makers, with athletes` preferences central. Findings support defining RTS as a continuum of phases and adopting a biopsychosocial, criteria-based, and shared decision-making approach. Consensus on relevant factors and athlete preferences is needed to guide future research, including trials and longitudinal studies assessing the efficacy of RTS protocols for musculoskeletal injuries.